2019
DOI: 10.1080/1478422x.2019.1645802
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al2O3reinforcement and precipitates on corrosion behaviour of 2618 and 6061 aluminium MMCs

Abstract: The corrosion resistance features of two different Metal Matrix Composites based on 6061 and 2618 aluminium alloys reinforced by 20% Al 2 O 3 particles by stir casting process, were studied in 3.5% NaCl and compared. The composites and their respective base alloys were characterised in terms of microstructure by optical and scanning electron microscopy and in terms of corrosion resistance by polarisation curves and electrochemical impedance. Results show how the presence of Al 2 O 3 has different effects depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the present scenario, aluminium based MMNC possess excellent specific strength and weight properties best suited to be used as structural members in aerospace industry and automotive industry [2]. Because of the optimal combination of ductility and high strength aluminium based MMNC have many application areas.…”
Section: Metal Matrix Nanocomposites (Mmnc)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present scenario, aluminium based MMNC possess excellent specific strength and weight properties best suited to be used as structural members in aerospace industry and automotive industry [2]. Because of the optimal combination of ductility and high strength aluminium based MMNC have many application areas.…”
Section: Metal Matrix Nanocomposites (Mmnc)mentioning
confidence: 99%
“…In last some decades light metal matrix composites (MMCs) materials having ceramic reinforcement particles have received widespread attention because of having superior mechanical properties over the base materials and found many interesting applications [1], [2]. Behaviour of alumina Al2O3 particles present in the MMC play an important role in deciding the overall properties of such composites [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the addition of whiskers will increase the corrosion phenomenon. Bragaglia et al [17] pointed out that the presence of alumina reinforcements may have various effects on the corrosion resistance of copper-based composites. This strengthening slows down the formation of the passivation film and weakens its protective effect.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Al 2 O 3 whiskers will increase the self-corrosion potential of copper matrix composite materials, making the materials vulnerable to pitting attack. Bragaglia et al [17] studied the effect of Al 2 O 3 strengthening and precipitation on the corrosion behavior of metal matrix composites, and pointed out that the comparison with data of unreinforced alloys confirmed that the presence of alumina has a small improvement in corrosion resistance [27]. Although pitting begins with the reinforcement phase/matrix, as the content of alumina whiskers increases, alumina, graphite, etc are exposed outside the matrix, which will limit the electrical connection between the intermetallic compound particles and the solution, and thus the reaction speed can be slow down.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation